Adobe XD CC classroom in a book 2019 release - Wood, Brian (Adobe instructor) (Classroom in a book., 2019)
"Creative professionals, web designers, and UX professionals seeking the fastest, easiest, most comprehensive way to learn Adobe XD (2020 release) choose Adobe XD Classroom in a Book (2020 release) from the best-selling series of hands-on software training workbooks from Adobe Press. The 11 project-based lessons in this book guide users step-by-step through key techniques in XD for designing and prototyping cutting edge content for websites, mobile apps, and presentations. You'll set up a project, create graphics, add images and text, organize content, and work with components and Libraries. You'll learn how to add effects and work more efficiently with repeat grid. You'll also create fully functioning prototypes, and explore how to preview, share, comment, and export production-ready assets."--Publisher